Issues in Arabic Speaking Skills: A Psycho-Sociolinguistic Approach - Amy Fitriani Siregar; Agung Setiyawan; Wafa’ Rizqiyya Adira; Ahmad Rizki Ramadhan; Zaffa Izzatul Islamiah; Bellah Asa O’Neal Elmi; Hafidz Shiddiq Hamonangan Lubis (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
This research aimed to analyze the issues in Arabic language leaners speaking skill through psycho-sociolinguistics. This qualitative literature research explored four main categories of issues in Arabic speaking skills: phonological errors, sentence structure differences, reduplication form deviations, and socio-cultural and bilingual influences. The results of this research highlighted the complexity of mastering Arabic speaking skills, which was influenced by innate psycho-sociolinguistic factors. This research contributed to a deeper understanding of the challenges faced by non-native Arabic speakers and aimed to help learners reflect on and improve their Arabic speaking skills. By understanding these issues, Arabic language learners will be able to anticipate and address the issues as they hone their speaking skill.